2022
DOI: 10.3390/medicina58070925
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Phagocytic Index of Peripheral Leukocytes in Endometriosis by Plasma Experiments

Abstract: Background and Objectives: Endometriosis is a benign, chronic disease, that negatively influences the quality of life of affected women and is responsible for a remarkable amount of infertility. The pathophysiology of the disease is still not clarified, but the insufficient immune surveillance plays a significant role in it. The phagocyte function of innate immune cells may play a role in the elimination of ectopic endometrium. The purpose of this study is to examine the phagocyte function of neutrophil granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Hematological blood tests were carried out on a hematological analyzer "Celly 70", ESR was established by the Panchenkov method, blood smears were stained by Papenheim, differential counting of leukocytes was carried out according to generally accepted methods [23]. The phagocytic activity index (percentage of phagocytic neutrophils) and phagocytic index (average number of microbes phagocytized by one neutrophil) were calculated [24]. Bacteriological flushes from the nasal cavity were collected with sterile cotton swabs into bacteriological tubes with sterile saline solution during the period of maximum manifestation of signs of the disease.…”
Section: Methodsmentioning
confidence: 99%
“…Hematological blood tests were carried out on a hematological analyzer "Celly 70", ESR was established by the Panchenkov method, blood smears were stained by Papenheim, differential counting of leukocytes was carried out according to generally accepted methods [23]. The phagocytic activity index (percentage of phagocytic neutrophils) and phagocytic index (average number of microbes phagocytized by one neutrophil) were calculated [24]. Bacteriological flushes from the nasal cavity were collected with sterile cotton swabs into bacteriological tubes with sterile saline solution during the period of maximum manifestation of signs of the disease.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported increased neutrophil concentrations in plasma and peritoneal fluid during EMS. Moreover, the phagocytic ability of neutrophils is significantly reduced ( Lukács et al., 2022 ). Studies have shown that SCFAs can enhance the phagocytosis of neutrophils at sites of inflammation by activating the GPR43 receptor ( Vinolo et al., 2009 ).…”
Section: Inhibition Of Ems By Scfas Relevant Mechanismsmentioning
confidence: 99%
“…Additionally, the miR-142-3p investigated in endometriosis studies and its role in disrupting antigen presentation by primary macrophages can attract attention to be investigated in future research ( 92 , 93 ). Although phagocytosis ( 94 ) and antigen presentation ( 78 ) are actions performed by macrophages during this disease, additional investigations using imaging techniques, suppression and upregulation of ncRNAs can shed light on the examination of cellular remodeling and migration of these cells.…”
Section: Non-coding Rnas Have Roles In the Inflammation And Immunopat...mentioning
confidence: 99%